LEGAL MECHANISM FOR CONTROLLING INVESTMENTS IN STRATEGICALLY IMPORTANT COMPANIES - Moroz, Victor P. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the article is devoted to the analyze of the legal mechanism of state control over investments in strategically important companies. Research methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical etc. Results: the concept of investment control, constituent elements of legal mechanism of investment control, the problems of introduction of this mechanism in Ukraine, its origin and historical genesis are analyzed, the comparative analysis of the legal mechanism of investment control in the legislation of Ukraine and other countries is executed. Discussion: the analysis of the legal mechanism of control over investments in strategically important companies is carried out.